Evaluating the effect of plantlet age and Trichoderma spp. application on acclimatization of Boehmeria nivea L. Gaud - Aprilia, Eva; Nuraini, Anne; Kadapi, Muhamad (Universitas Padjadjaran, 2024)
One of the crucial stages in the ramie plant (Boehmeria nivea L. Gaud) tissue culture is the acclimatization phase, which transitions between the in vitro and ex-vitro environments. Determining the appropriate age of plantlets and providing nutrients in the substrate play significant roles in the success of acclimatization. This research is conducted to determine the most suitable age of plantlets for acclimatization and assess the impact of providing nutrients through Trichoderma spp. application on the growth of ramie seedlings during the acclimatization phase. The experiment was conducted between January and March 2023 at the Screenhouse Bale Tatanen, Faculty of Agriculture, Universitas Padjadjaran, Jatinangor, Sumedang. The experimental design used was a Randomized Complete Block Design (RCBD) with two factors: plantlet age with three levels (4, 8, and 12 weeks old) and Trichoderma spp. fertilizer application with two levels (without and with Trichoderma) with 4 replications. The results showed that the 4-week-old plantlets exhibited the best height, root number, root length, and leaf number growth. Additionally, the application of Trichoderma spp. increased the stem diameter of the ramie seedlings during the acclimatization phase.